Webinar STOP HIV Pada Pendonor Darah Menuju Triple Zero HIV 2030 - Francisca Romana Sri Supadmi; Nur’Aini Purnamaningsih (Jurnal Pengabdian Pada Masyarakat, 2022)
WEBINARS: STOP HIV ON BLOOD DONORS TOWARDS TRIPLE ZERO HIV 2030. The various elements of society continue to strive to support the global HIV program, to end the spread of HIV by 2030. In order to break the chain of HIV spread, one of the efforts is the STOP HIV method. The step that can be taken by the Blood Transfusion Unit (UTD) is to find someone who is infected with HIV through a blood donor for further treatment and treatment. The purpose of this community service is to provide an overview and increase knowledge about HIV disease, how to break the chain of spread using the STOP method to the target group of health workers who work in the blood service unit. Stages of activities include planning, implementation, and evaluation. At the preparatory stage, a preliminary study was conducted, to collect information related to the understanding of potential participants on HIV, submit proposals, and permits and coordinate with resource persons. At the implementation stage, a pre-test was carried out before the activity, followed by the provision of education related to HIV with three different sources, ending with a post-test. The final stage of the activity, carried out data analysis and reporting the results of service. The service participants totaled 163 participants consisting of blood service technicians, HIV counselors, UTD doctors, and students. After the webinar, there was an increase in participants' understanding of HIV, which was originally the average score of the pretest result of 60, increased to 71.42 in the post test result.